Equal Rights, Vol. 12, No. 19, June 20, 1925 - National Woman's Party (Washington D.C.: National Woman's Party, 1925)
National Woman's Party. Equal Rights, Vol. 12, No.19, June 20, 1925. Equal Rights Newsletter (MS-144). Valdosta State University Archives and Special Collections. Search the Equal Rights Index at https://archives.valdosta.edu/findingaids/indexes/equal-rights-index.html
National Woman's Party. Equal Rights, Vol. 12, No.19, June 20, 1925. 1 PDF file, 5 scans.
Keywords: Newsletters; Suffragists; Women's rights; National Woman's Party